PENGARUH PENAMBAHAN BAYAM MERAH PADA OLAHAN PEMPEK IKAN TENGGIRI DITINJAU DARI SIFAT ORGANOLEPTIK DAN KADAR ZAT BESI (Fe) - Novianty Novianty (Masker Medika, 2023)
Introduction: Pempek is a typical Palembang food whose main ingredients are fish meat and starch (tapioca flour). Pempek with the addition of red spinach can be put to good use as an alternative food source of iron. Purpose: aims to determine the effect of adding red spinach on organoleptic properties and levels of iron (Fe) in mackerel pempek. Methods: This study was an experimental study using a non-factorial Completely Randomized Design (CRD) with 2 repetitions. Treatment in the form of the addition of red spinach as much as 0%, 15% and 25%. The panelists used in this study were 30 semi-trained panelists. Analysis of the results of the organoleptic test used the Normality test with Excel while the results of the iron content test used the ANOVA and DMRT (Duncan Multiple Range) tests. Conclusion: (1) It is known that the acceptability of processed mackerel pempek based on color, aroma and taste assessment is more preferred by the panelists is P0 (Control) without the addition of red spinach with an average color result of (5.9), aroma of (5 ,6) and taste of (5,9) while based on texture assessment the panelists preferred P1 with the addition of 15% red spinach with an average texture yield of (5,8). (2) Based on the results of laboratory tests, it was known that the level of pempek with the addition of red spinach which had the highest iron content was pempek with the addition of 25% red spinach, which was 1.22 mg/100 g (P2) compared to (P1), which was 1.08 mg/100 g . And the ratio of iron levels between the two is equal to 0.14 mg.